A study combining magic-angle spinning NMR and small-angle X-ray scattering on the interaction in the mixture of poly(benzyl methacrylate) and ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)amide. Issue 43 (26th October 2022) - Morita, Takeshi; Okada, Hitomi; Yamada, Taisei; Hidaka, Ryo; Ueki, Takeshi; Niitsuma, Kazuyuki; Kitazawa, Yuzo; Watanabe, Masayoshi; Nishikawa, Keiko; Higashi, Kenjirou
Abstract : Despite being an LCST system, the NMR results indicate that the number of ionic liquid ions interacting with the solute polymer increases even at temperatures approaching the separation line. Abstract : A mixture of poly(benzyl methacrylate) (PBnMA) and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)amide ([C2 mim][NTf2 ]) exhibits lower-critical-solution-temperature (LCST)-type phase separation. An investigation combining magic-angle spinning NMR spectroscopy and small-angle scattering was performed to gain new insights into the interaction between PBnMA and the ionic liquid. The molecular mobility and the solute–solvent interaction in the system were investigated using 1 H high-resolution magic-angle spinning NMR. Applying a magic-angle spinning frequency of 2 kHz allowed identifying the PBnMA peaks, which were not observed by conventional solution-state NMR. The peaks of [C2 mim] + almost coincided in the presence and absence of PBnMA, indicating the decoupling of the bulk solvent and polymer. The conformational state of PBnMA in [C2 mim][NTf2 ] was investigated using small-angle X-ray scattering (SAXS). The pair distribution functions of PBnMA chains calculated from SAXS profiles suggest that PBnMA adopts a random coil conformation upon dissolution in [C2 mim][NTf2 ]. The combined study clarifies the decoupled low mobility of polymers with a random coil conformation. It is considered that the specific decoupled low mobility is one of the origins of the decoupling conductivity of [C2 mim][NTf2 ] in a matrix polymer. In addition, an increase in temperature induced a downfield shift and broadening of the [C2 mim] + peaks, suggesting that a larger amount of [C2 mim] + was bound to the PBnMA chains even at temperatures approaching the LCST.